Pengaruh Terapi Bermain Storytelling Dengan Media Hand Puppet Terhadap Kecemasan Hospitalisasi Anak Usia Pra Sekolah Di RSUD dr. R. Goeteng Taroenadibrata Purbalingga - Ferra Dita Larasaty; Sodikin Sodikin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To find out the effects of hand puppet storytelling therapy towards hospitalization anxiety on preschool children in RSUD dr. R. Goeteng Taroenadibrata Purbalingga.Method: This was a quantitative research with pre-experimental design and one group pretest - post test approach. The samples of this research were 30 respondents selected using consecutive sampling technique. The instrument of this research was questionnaire of FAS (Faces Anxiety Scale) and the data were analyzed using paired sample t test.Results: The results showed the pre intervention anxiety score was 3,76to0,67891 and post intervention anxiety score was 1,63to0,80872 which meant hand puppet storytelling therapy was effective to reduce hospitalization anxiety on preschool children in RSUD dr. R. Goeteng Taroenadibrata Purbalingga in intervention group(p=0.0001).Conclusion: Hand puppet storytelling therapy was effective to reduce anxiety on hospitalized preschool children.